The Mom's Cerij Oil to Maintain Skin Moisture and Prevent Striae Gravidarum in Second Trimester - Fika Maulina; Leri Septiani; Yanti Herawati; Herri S Sastramihardja; Meti Widya Lestari; Teni Nurlatifah (Poltekkes Kemenkes Surakarta, 2026)
Background: Skin changes often occur during pregnancy, such as striae gravidarum and hyperpigmentation. Mom’s Cerij Oil is formulated to minimize the risk of allergies or skin irritation, making it suitable for sensitive skin during pregnancy. The aim of this study was to determine the effectiveness of Mom’s Cerij Oil (Centella Asiatica and Piper betle L) compared to Coconut Oil in maintaining skin moisture and preventing Striae Gravidarum in pregnant women in the second trimester at the Cikupa Health Center in Tangerang Regency. Methods: The research method was a quantitative study using a true experimental design with a pretest-post test control group approach. The study involved 66 pregnant women in their second trimester at the Cikupa Health Center in Tangerang Regency. The sampling technique used purposive sampling, with each intervention group and control group consisting of 33 respondents. Data analysis involved univariate analysis using frequency distribution and bivariate analysis using the McNemar test and the Mann–Whitney U test. The study was conducted from January to February 2025. Results: Bivariate analysis showed that Mom’s Cerij Oil was effective in maintaining skin moisture and preventing striae gravidarum in second-trimester pregnant women, with significant pretest–posttest mean differences (0.42; p=0.039 and 0.18; p=0.031). Posttest comparison between Mom’s Cerij Oil and coconut oil groups also indicated a significant difference (p=0.001). Conclusion: Mom’s Cerij Oil is more effective than coconut oil in maintaining skin moisture and preventing striae gravidarum in second-trimester pregnant women, and it can be recommended as a safe topical option during pregnancy.